Serological profiling and molecular detection of variant D in rhesus negative blood donors in Perak - Ponnusamy, Shalini (2017)
D variant individual has the potential to cause anti-D production resulting in hemolytic transfusion reactions and hemolytic disease of the fetus and newborn. However, D variants are usually under detected and mistyped as Rhesus D (RhD) negative due to limitations of the available serological tests. Hence it is important to solve serological discrepant cases and further accurately classify D variants by molecular testing. In view of this, the aim of this study is to identify the frequency of D variant among the RhD negative blood donors in this population using serological and molecular tests. A total of 175 RhD negative donors were recruited through mobile drives and collection centres in Hospital Raja Permaisuri Bainun from September 2015 till March 2016. Serologically, ABO blood grouping and RhD typing was done with monoclonal antibody, IgM (TH-28), Diaclone (Diamed) using the microtitre plate and IgM/IgG, EpicloneTM-2 (CSL) using the tile and tube method. Other Rh typing was done with the anti-c/C/E/e IgM/IgG, EpicloneTM-2 (CSL). Weak D or Du test was done using tube method with IgM/IgG blend, EpicloneTM-2 (CSL). Molecular testing using Polymerase Chain Reaction – Sequence Specific Primer (PCR-SSP) to detect DEL variant (RHD 1277A or K (409) K mutation) were done on all samples while BAGene RH TYPE kit and Partial D TYPE kit (commercialized kits) were performed on Du positive samplesand positive RHD 1277A/ K(409)K samples by Polymerase Chain Reaction – Sequence Specific Primer (PCR-SSP). The most common RhD negative blood group was O (46.9%) followed by B, A and AB. The ccddee (81.7%) is the most common phenotype among RhD negative donors and most common phenotype in all races. The Ccddee phenotype was common among the Chinese (43.8%). Serologically by Du test, 6 (3.4%) were found to be D variant with phenotypes CDe/cde (4), CDE/cDe (1), and CDe/CDe (1). Molecular test revealed a total of 10 donors with D variants in which 3 with RHD 1277A/K (409) K (all these belonged to Chinese), 5 with Partial D (unclassified), 1 with Partial DVI type III and 1 with RHD-CE(2–9)-RHD. In conclusion, the prevalence of variant D among RhD negative donors was found to be low (3.4%). Serological testing was able to detect most partial D variants but not DEL variants. Only molecular testing is able to detect DEL variant (RHD 1277A / K (409) K). Molecular test is advised on RhD negative Chinese’s with Ccddee phenotype, since the frequency of RHD DEL 1277 K (409) K is high among them.